2016
DOI: 10.1093/annonc/mdw012
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of neutrophil-to-lymphocyte ratio in advanced oesophago-gastric cancer: exploratory analysis of the REAL-2 trial

Abstract: Our results confirm that high NLR status had a significant negative prognostic effect in the REAL-2 trial population. Based on the multivariate analysis, this effect was independent of other known prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 18 publications
4
59
0
Order By: Relevance
“…Based on these studies, we analysed CRP and albumin levels in the present NEC cohort, however neither CRP nor albumin levels were prognostic factors in this population. The NLR reflects the immune status of patients and a high NLR is associated with poorer survival in biliary tract cancer8 and in gastric cancer7. After analysis of NLR with the two cut-off levels used in other studies, neither a cut-off value of 3 or 4 were prognostic factors in this population.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Based on these studies, we analysed CRP and albumin levels in the present NEC cohort, however neither CRP nor albumin levels were prognostic factors in this population. The NLR reflects the immune status of patients and a high NLR is associated with poorer survival in biliary tract cancer8 and in gastric cancer7. After analysis of NLR with the two cut-off levels used in other studies, neither a cut-off value of 3 or 4 were prognostic factors in this population.…”
Section: Discussionmentioning
confidence: 78%
“…The NLR was calculated and was considered high if NLR ≥ 378 or ≥ 4 25. For all statistical analysis of biological data, we first analysed the median value as a cut-off.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many organ systems act in the activation of systemic inflammatory responses, the common measurements of the magnitude of activation are circulating cellular components and acute-phase proteins. In particular, several common peripheral blood-derived inflammation-based scores, such as the Glasgow Prognostic Score (GPS), NLR, and PLR, have been demonstrated as promising prognostic predictors in various malignancies 2628. However, the measurement of serum C-reactive protein was not routinely taken in our hospital before 2005, and therefore, the prognostic value of GPS was not examined in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…However, ICC often presents at an advanced stage, and in some series only 15-20% of the patients have resectable tumors [15]. Patients with advanced BTC have an ex- [5,7,18,19]. Phase II and III trials were conducted in 2010 in patients with advanced BTC including ICC, and a meta-analysis showed that ICC patients benefited more from GC therapy than did those patients with other BTC tumors [20].…”
Section: Discussionmentioning
confidence: 99%